Analysis of Factors Influencing the Quality of Islamic Education at MI Bahrul Ulum Rangkap II Kuta - Saputra, Mahendra; Nuruddin, Nuruddin; Sulhan, Ahmad; Hakim, Lukman (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This journal was written by the author to examine the factors that influence the systemic thinking paradigm in Islamic education. Furthermore, this article was written using qualitative writing methods and literature studies or Library Research. The results of this study show that paradigms, thinking and systems influence Islamic education. To improve the quality of Islamic education, the paradigm must be able to position it as the most important system component for the institution to educate the whole human being (insan kamil). There are methods of thinking and if applied in Islamic education then through these methods, whether carried out alternatively or in an integrated manner, not only can it touch on the issues of hablu min Allah and hablu min al-'alam, but will also add to the hablm min annas or problems -social issues in Islamic education. Islamic education must have a complex system so that it will make it easier for Islamic education to achieve the targets, goals, mission and vision of the Islamic education system to be able to compete with current developments in the era of globalization. Government policy has a very important influence on Islamic education. The existence of government policies is very helpful in carrying out and implementing the management function of Islamic education itself. In this way, we can achieve the goals, mission and vision of Islamic education that are valuable in the world of education.